Inclusion of Web Intelligence with Brain Informatics: Exploring the Synergy between Web Intelligence and Brain Informatics (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A vision of Web Intelligence (WI) research from the viewpoint of Brain Informatics (BI), a new interdisciplinary field that systematically studies the mechanisms of human information processing from both the macro and micro viewpoints by combining experimental cognitive neuroscience with advanced information technology. BI studies human brain from the viewpoint of informatics (i.e., human brain is an information processing system) and uses informatics (i.e., WI centric information technology) to support brain science study. Advances in instrumentation, e.g., based on fMRI and information technologies offer more opportunities for research in both Web intelligence and brain sciences. Further understanding of human intelligence through brain sciences fosters innovative Web intelligence research and development. WI portal techniques provide a powerful new platform for brain sciences. The synergy between WI and BI advances our ways of analyzing and understanding of data, knowledge, intelligence, and wisdom, as well as their interrelationships, organizations, and creation processes. Web intelligence is becoming a central field that revolutionizes information technologies and artificial intelligence to achieve human-level Web intelligence.